PEMBERDAYAAN KADER KESEHATAN PADA POSYANDU LANSIA DI DUSUN MLANGI, NOGOTIRTO, GAMPING, SLEMAN - Nor Faizah Kaeni; Diyah Candra Anita K; Andri Nur Sholihah (CV. Multi Kreasi Media, 2022)
Healthy community life can reduce morbidity and mortality rates and increase life expectancy. One of the health qualities of an area is the high life expectancy. There needs to be detection related to blood pressure, uric acid levels and blood sugar which results in a decrease in the ability of the body's organs to decline rapidly. Community service in this period was carried out at the Elderly Posyandu in Mlangi Hamlet, Nogotirto, Gamping, Sleman with various kinds of problems. This activity aims to improve the quality of life of the community, so that they can live healthy and happy lives. The form of this activity is the formation of the Elderly community, counseling to monitoring activities from the community for approximately 4 months in 2020. The Posyandu for the elderly is a form of activity from the elderly community that has been successfully implemented. This activity is driven by cadres who have been recommitted to revive this Posyandu activity for the elderly.